Pengaruh Kompetensi, Kompensasi, Disiplin Kerja terhadap Kinerja Guru pada Lazuardi Global Islamic School - Asep Suherman (Research Center and Case Clearing House PPM School of Management, 2021)
The purpose of this study was to determine the effect of competency variables, compensation, work discipline partially and simultaneously on teacher performance. The method used in this research is quantitative descriptive analysis with multiple regression tests using the SPSS version 22 program. The population in this study was 105 teachers at Lazuardi Global Islamic School. The results of this study indicate that partially competence and compensation have a positive and significant effect on teacher performance, but work discipline does not significantly affect teacher performance. Furthermore, simultaneously, the competency, competence, and work discipline variables together have a significant effect on teacher performance. The suggestions given based on the results of this study are that teachers should improve their competence in the teaching and learning process, school management should increase compensation in the form of financial incentives for teachers, the level of teacher discipline is good enough, but teachers should improve their communication with school management if they face a problem. , because from the research results the discipline variable has not affected performance, efforts to discipline teachers in the teaching and learning process must be a priority program of school management